1995
DOI: 10.3109/00048679509075897
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorder Patients at a NSW Teaching Hospital: A Comparison with State-Wide Data

Abstract: The aim of the study was to present data which may be useful in deciding the type of services needed for eating disorder (ED) patients in New South Wales (NSW). The demographic and clinical characteristics of 155 patients consecutively admitted to a special ED unit at a major Sydney teaching hospital during the triennium 1989-1991 were documented and compared with relevant data from the State as a whole (709 admissions for ED to public facilities and 938 admissions for ED to private facilities during the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…A total of 40 individuals who did not meet full criteria for anorexia nervosa or bulimia nervosa were excluded. Inspection of the EDE-Q, age and BMI data indicated that individuals in this subgroup were primarily cases of partial-syndrome anorexia, as in other clinical samples [5]. Data from eight individuals who did not meet full criteria for binge eating disorder were also excluded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 40 individuals who did not meet full criteria for anorexia nervosa or bulimia nervosa were excluded. Inspection of the EDE-Q, age and BMI data indicated that individuals in this subgroup were primarily cases of partial-syndrome anorexia, as in other clinical samples [5]. Data from eight individuals who did not meet full criteria for binge eating disorder were also excluded.…”
Section: Resultsmentioning
confidence: 99%
“…The World Health Organization Quality of Life Assessment Group was formed in response to the perceived need for development of a purely subjective measure [33], while others have argued for a greater reliance on more 'contextual' factors, such as standard of living, levels of autonomy and access to social support, particularly in the assessment of patients suffering from schizophrenia and related disorders [32]. Such factors may be less relevant in eating disorder patients, who are typically not economically disadvantaged [5]. Measures of HRQoL, which combine both subjective and objective elements, might be considered to lie somewhere in between these poles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of males identified in clinic-based case series has generally been substantially smaller than the proportion identified in community-based samples (Lucas et al, 1991;Carlat & Camargo, 1991;Beumont, Schrader, & Lennerts, 1995). This discrepancy has caused speculation that males may be less likely to seek treatment for eating disorders than their female counterparts (Carlat & Camargo, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Cases of eating disorders presenting for treatment place a considerable strain on health services because of high levels of clinical load (patient days), high levels of comorbidity with anxiety and affective disorders, and high rates of relapse. 5,6 Medical complications of anorexia nervosa (AN), including loss of menstruation, are a consequence of severe weight loss and may be life-threatening. However, AN is uncommon and affects primarily adolescent girls.…”
mentioning
confidence: 99%